COMPETENCY-BASED LANGUAGE INSTRUCTION IN SPEAKING CLASSES: ITS THEORY AND IMPLEMENTATION IN INDONESIAN CONTEXTS - Marcellinus Marcellino (Universitas Katolik Indonesia Atma Jaya, 2005)
The competency-based curriculum as endorsed by the Department of Education and Culture of the Republic of Indonesia has recently been implemented nationwide from elementary to high schools in the country. It is claimed that by improving syllabi, materials, and activities or by putting a more emphasis on learners’ autonomy, more effective language learning will take place. However, such an approach may also be counter-productive as it emphasizes the outputs more than the inputs. Another problem may arise as learners’ language performance may also entail teaching preparations in that teachers are obliged not only to be knowledgeable of the topics discussed, but also to be skillful and creative in preparing the materials. The implementation of this approach then becomes more complicated, especially when related to the learners’ culture. The features of this language instruction seem to be contradictory to Indonesians’ cultural values and beliefs which are reflected in the forms of total obedience, the unquestioning mind, the concept of the old know all, and the teachers can do no wrong.Due to the above barriers, this study intends to explore and evaluate the effectiveness of the implementation of this instruction in speaking classes in Indonesian contexts. It will specifically attempt to assess the extent to which closed and open tasks can affectively be accomplished and with what degree of success the students acquire natural language use. Keywords: Competency-based curriculum, output, input